(+)-Epogymnolactam, a novel autophagy inducer from mycelial culture of Gymnopus sp. (June 2015) - Mitsuhashi, Shinya; Shindo, Chihaya; Shigetomi, Kengo; Miyamoto, Toshizumi; Ubukata, Makoto
Graphical abstract: An autophagy inducer, named (+)-epogymnolactam, was discovered from the mycelial culture of Gymnopus sp., and exists as a tautomeric mixture. The major form in MeOH was (1 R, 5 S )-4-butyl-4-hydroxy-3-aza-6-oxa-bicyclo[3.1.0]hexan-2-one. Highlights: (+)-Epogymnolactam (1 ), an autophagy inducer, was isolated from a Gymnopus sp. Its structure was determined by MS, NMR, and by specific rotation. It exists as a tautomeric mixture in MeOH. The major tautomer form was (1 R, 5 S )-4-butyl-4-hydroxy-3-aza-6-oxa-bicyclo[3.1.0]hexan-2-one. The minor tautomeric form was (2 R, 3 S )-3-pentanoyloxirane-2-carboxamide. Abstract: Mushrooms, including Ganoderma lucidum, have been used as a potential source of therapeutic compounds, and an autophagy inducer would be useful for treatment of diverse diseases in human. Reported here is a full account of screening, isolation, structural determination, and biological activity of an autophagy inducer, (+)-epogymnolactam (1 ) from a mycelial culture of a Gymnopus sp. strain. Its structure was elucidated by HR-ESI-MS, NMR, and its plus sign by specific rotation. It exists as a tautomeric mixture of 1a and 1b in MeOH. The major tautomer of 1 is (1 R, 5 S )-4-butyl-4-hydroxy-3-aza-6-oxa-bicyclo[3.1.0]hexan-2-one (1a ), and the minor tautomeric form is (2 R, 3 S )-3-pentanoyloxirane-2-carboxamide (1b ).